2014
DOI: 10.1007/s10278-014-9744-6
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technology for Automatically Obtaining Digital Facial Photographs Near-Simultaneously with Portable Radiographs

Abstract: Our objective is to design, implement, and phantom-test a device to automatically obtain point-of-care patient photographs along with portable radiographs. Such photographs could help with detection of wrong-patient errors. Our device consists of a camera controller (CC) and a camera that can be mounted on a portable conventional radiography (CR) machine. Radiation from the CR machine triggers an identification module (IM) embedded in the CR cassette. The IM then sends the cassette identifier-Plate_ID-to the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Finally, 41 and 57 % of technologists anticipated spending more time in obtaining the radiographs or encountering technical or software issues with the new technology, respectively. This process has been shown in a prior pilot study to be automated for portable radiographs so that there is no extra work for the technologist at the time of the chest portable studies [18]. Thus any new technology that incorporates photographs with medical imaging is more likely to be accepted if it does not slow down technologists or adversely impact workflow.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, 41 and 57 % of technologists anticipated spending more time in obtaining the radiographs or encountering technical or software issues with the new technology, respectively. This process has been shown in a prior pilot study to be automated for portable radiographs so that there is no extra work for the technologist at the time of the chest portable studies [18]. Thus any new technology that incorporates photographs with medical imaging is more likely to be accepted if it does not slow down technologists or adversely impact workflow.…”
Section: Discussionmentioning
confidence: 99%
“…A general overview of the camera technology is provided by Ramamurthy et al (5), and further details regarding its operation have been described by Ramamurthy et al (6) and Tridandapani et al (7). A small camera is mounted on the x-ray head of the portable radiography machine.…”
Section: Camera Technology In Briefmentioning
confidence: 99%
“…Motivated by a need to increase the detection rate for wrong-patient errors in radiology (1-4), we developed a technology to automatically obtain point-of-care patient photographs along with portable radiographs (5)(6)(7). Observer studies in controlled laboratory-like settings demonstrated that the addition of patient photographs to portable chest radiographs can increase the detection of wrong-patient errors, without substantially increasing interpretation time (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%